The Effect of Profitability, Leverage, Firm Size, and Liquidity on Firm Value in The Processed Food Subsector Listed on The Indonesia Stock Exchange for The Period 2015-2024 - Rani Indriawati; Hirdinis Mansyur (Universitas Mercu Buana, 2026)
The purpose of this study is to examine how firm value in the processed food subsector listed on the Indonesia Stock Exchange between 2015 and 2024 is affected by profitability, leverage, business size, and liquidity. This study uses a quantitative technique and a causality research design. Purposeful sampling was used to choose ten of the 19 processed food companies listed on the Indonesia Stock Exchange as the sample. EViews 13 software was used to process 100 observations of secondary data from annual financial statements. Panel data regression analysis is the data analysis technique used in this study to look at the association between variables. The findings demonstrate that business value as determined by Tobin's Q is positively and significantly impacted by profitability as determined by ROA. However, company size has a substantial negative impact on firm value. However, the DER and CR, which are stand-ins for leverage and liquidity, have no effect on corporate value. Keyword: profitability, leverage, firm size, liquidity, firm value